Molecular diagnosis and genetic diversity of tick-borne Anaplasmataceae agents infecting the African buffalo Syncerus caffer from Marromeu Reserve in Mozambique - Machado, Rosangela Zacarias [UNESP] (2016)
Background: Tick-borne diseases (TBDs) are very important in relation to domestic ruminants, but their occurrence among wild ruminants, mainly in the African buffalo Syncerus caffer, remains little known. Methods: Molecular diagnostic methods were applied to detect Anaplasma marginale, Anaplasma centrale, Anaplasma phagocytophilum, Ehrlichia ruminantium and Ehrlichia chaffeensis in 97 blood samples of African buffalo captured at the Marromeu Reserve in Mozambique. Molecular detection of agents belonging to the family Anaplasmataceae were based on conventional and qPCR assays based on msp5, groEL, 16S rRNA, msp2, pCS20 and vlpt genes. Phylogenetic reconstruction of new Anaplasma isolates detected in African buffalo was evaluated based on msp5, groEL and 16S rRNA genes. Results: All the animals evaluated were negative for specific PCR assays for A. phagocytophilum, E. ruminantium and E. chaffeensis, but 70 animals were positive for A. marginale, showing 2.69 × 100 up to 2.00 × 105 msp1β copies/μl. This result overcomes the conventional PCR for A. marginale based on msp5 gene that detected only 65 positive samples. Sequencing and phylogenetic analyses were performed for selected positive samples based on the genes msp5, groEL and 16S rRNA. Trees inferred using different methods separated the 29 msp5 sequences from buffalo in two distinct groups, assigned to A. centrale and A. marginale. The groEL sequences determined for African buffalo samples revealed to be more heterogeneous and inferred trees could not assign them to any species of Anaplasma despite being more related to A. marginale and A. centrale. The highly conserved 16S rRNA gene sequences suggested a close relationship of the new 16 sequences with A. centrale/A. marginale, A. platys and A. phagocytophilum. Conclusions: Our analysis suggests that different species of Anaplasma are simultaneously present in the African buffalo. To the best of our knowledge, this is the first study that diagnosed Anaplasma spp. in the African buffalo and inferred the taxonomic status of new isolates with different gene sequences. The small fragment of msp5 sequences revealed to be a good target for phylogenetic positioning of new Anaplasma spp. isolates.